Molecular Diagnosis of Non X-linked Ectodermal Dysplasias Using Next Generation Sequencing - Rabie, Eman AbdelAlim (AUC Knowledge Fountain, 2023)
Ectodermal Dysplasias (EDs) are rare heterogenous monogenic developmental disorders sharing the impairment of at least two surface ectoderm-derived organs. Symptoms characteristically manifest developmental abnormalities of the teeth, and three skin derivatives: hair follicles, nails, and sweat glands. The disease-causing gene was identified for only fewer than half of 160 characterized ED phenotypes. Expectedly, ED-causing genes regulate or function in ectodermal-developmental processes. The most common phenotype is hypohidrotic ED featuring teeth agenesis, and diminished or complete absence of hair and sweat production. Disease-causing variants of EDA, EDAR, EDARADD and WNT10A genes were identified in 60-90% of ED patients in a handful of cohorts, mostly of European origins. The current study explores the contribution of the four abovementioned genes using targeted NGS panel in a cohort of 45 Egyptian ED patients. Only 28 patients (60%) were identified to have thirteen different ED-causing variants, the majority of them had X-linked EDA-causing variants. Distinctly, no WNT10A disease-causing variants were detected, and eight novel variants were identified: five EDA, one EDAR and two EDARADD variants. Some novel variants were predicted to affect previously uncharacterized protein domains, and some variants recurred in multiple unrelated patients. Whole exome sequencing (WES) was employed in molecularly unidentified cases. Four novel disease-causing variants were identified in TSPEAR -a gene recently added to the plethora of ED-causing genes- in ten patients (18%) who featured characteristic dysmorphic facies. Interestingly, a novel potentially founder TSPEAR in-frame deletion was identified in eight patients. Other rare potential disease-causing variants were identified in other genes, e.g., GREM2 and BTD while about 20% of cases remain unidentified. A tailored molecular diagnostic approach targeting specific fragments of EDAR, EDARADD and TSPEAR prior to WES was proposed in a second cohort of ten non X-linked Egyptian ED patients. Novel disease-causing variants were identified in nine patients, and new insights on proteins’ functionalities and genotype-phenotype relationships were projected. In conclusion, the current study expands the molecular, genetic and phenotypic landscape of ED, particularly in an underrepresented population of North Africa. The employment of targeted mutational analysis prior to WES provides proposedly rapid and cost-effective primary approach in ED diagnosis.